Assessing Trends in Women’s Violence via Data Triangulation: Arrests, Convictions, Incarcerations, & Victim Reports - Schwartz, Jennifer (Soc Probl, 2009)
Constructionist theories suggest the national rise in female violence arrests may be policy-generated because arrest statistics are produced by violent behavior and changing official responses (e.g., net-widening enforcement policies). Normative theories attribute the rise to female behavior changes (e.g., in response to increased freedoms or hardships). We examine whether any narrowing of the arrest gender gap is borne out across offense types of varying measurement reliability, in victimization data, and across two post-arrest criminal justice stages. Advanced time-series analyses over 1980–2003 support the constructionist position – first, all sources show little or no increase in women’s rates for the more reliably measured offenses of homicide and robbery, and for rape; second, the assault gender gap narrows for arrests, but holds stable in victimization data; third, the assault gender gap narrows moderately for convictions, but is stable for imprisonment, indicating spill-over effects of more expansive arrest policies. Several factors have produced greater female representation in “criminal assault” arrests including (i) proactive policing targeting and formally responding to minor violence and in private contexts, (ii) interventionist developmental epistemologies that blur distinctions among violence types and circumstances, (iii) the rise of social movements recognizing “hidden” victims, (iv) law and order political messages stressing greater accountability, and (v) the somewhat greater decline in male compared to female violence in the late 1990s. The problem of women’s violence is largely a social construction. Rather than women becoming more violent, changes in the management of violence increasingly mask differences in the violence levels of women and men.